Self-Perceived Employability of Workers With Disability: A Case Study in an Educational Farm - Fantinelli, Stefania; Di Fiore, Teresa; Marzuoli, Alessia; Galanti, Teresa (Frontiers in Psychology, 2022)
Background The job placement of persons with disability is often threatened by prejudices and stereotypes; even when they are employed, they have less qualified and less paid jobs. The aim of this study was to investigate the self-perceived employability in a sample of workers with disability, hypothesizing to find a good level of self-determination and positive meaning of work. Materials and Methods Ten semi-structured interviews have been conducted, applying a mix-method to the data analysis through qualitative interpretation and quantitative content analysis. Results confirmed what recent literature shows about the need for job inclusiveness for persons with disability and also underlined a profound sense of satisfaction related to the job, strong identity, and empowerment derived from the job involvement. Conclusion Practical implications are related to the job design procedure inspired by diversity management, in order to pay attention to every single diversity and ensure equity and inclusion.